Common pitfalls in statistical analysis: Measures of agreement - Priya Ranganathan; C S Pramesh; Rakesh Aggarwal (Perspectives in Clinical Research, 2017)
Agreement between measurements refers to the degree of concordance between two (or more) sets of measurements. Statistical methods to test agreement are used to assess inter-rater variability or to decide whether one technique for measuring a variable can substitute another. In this article, we look at statistical measures of agreement for different types of data and discuss the differences between these and those for assessing correlation.